STRATEGI PENYELAMATAN DAN PENYELESAIAN PEMBIAYAAN BERMASALAH PADA BANK SYARIAH - Tesya Widya Octavianti (2023)
The development of non-performing financing in Islamic banks has experienced significant developments. The greater the financing difficulties faced by banks, the soundness level of Islamic banks will decrease, a decrease in the quality of financing and the level of soundness of banks affects financial liquidity and solvency, which in turn can affect the trust of depositors and even prospective customers. Based on the provisions of Bank Indonesia, a healthy bank is a bank that shows a Non Performing Financing (NPF) value of less than 5%. If more than 5% then the bank is said to be unhealthy. In order for the NPF value to decrease, a restructuring is carried out after that a settlement of financing that has problems with bad collectability is carried out (5). Financing restructuring is an effort made by banks with the aim of helping customers to fulfill their obligations, including through rescheduling, reconditioning and restructuring. Settlement of problem financing can be done by means of settlement by the bank itself, through a debt collector (debt collector), through an auction at the auction office, or through a court of law.